GAMBARAN Q ANGLE TERHADAP LANSIA DI PANTI WERDHA BOGOR - Tisaningrum (2022)
The Q angle has been accepted as an important factor in assessing knee joint function. Decreased muscle strength in the elderly causes limitation of joint motion, decreased flexibility, and causes abnormal alignment of the knee. Abnormal alignment of the knee often occurs because of a change in the Q Angle from a normal position and causes an abnormal function of one of the stability produced by the Q Angle. The purpose of writing this Final Scientific Paper is to find out the description of Q Angle towards the elderly in several nursing homes in Bogor. This study is a descriptive study with a sample of 30 participants. The results of the study with the category of balance between right and left on the normal value of the Q Angle measurement with a percentage of 66.7% on the Balance of the Q Angle Value with the Normal Value. There is also an imbalance in the value of Q Angle with a normal value with a percentage of 3.3%. In the Balance category, the Q Angle Value but Exceeds the Normal Value has a percentage of 6.7%. 10% for the category of Imbalance of Q Angle Value but Exceeding the Normal Value and Imbalance of Q Angle Value with Different but Normal Values with a percentage of 13.3%.